Association Between State-Based and Trait-Based Responsiveness to Satiety Cues Differs by Child Risk for Overweight/Obesity. (7th June 2021) - Reigh, Nicole; Pearce, Alaina; Garavan, Hugh; Geier, Charles; Rolls, Barbara; Rose, Emma; Wilson, Stephen; Keller, Kathleen
Abstract: Objectives: The relationship between parentally reported satiety responsiveness (i.e., trait) and laboratory-assessed satiety responsiveness (i.e., state) in children is not known, making it difficult to interpret and generalize lab-based findings. In addition, while many studies have shown weight-related differences in children's eating behaviors, less is known about appetitive traits that are present before obesity develops. Therefore, we examined associations between trait- and state-based satiety responsiveness among children with healthy weight who differed by familial risk for obesity. Methods: Data from an ongoing longitudinal study were analyzed for 59 healthy-weight, 7–8 year-old children (BMI-for-age% < 85). Familial risk for obesity was determined by parental weight status as low-risk (N = 34, both parents' BMIs < 25 kg/m 2 ) or high-risk (N = 25, mothers' BMI ≥ 30 kg/m 2 ; fathers' BMI ≥ 25 kg/m 2 ). Parents completed the Children's Eating Behavior Questionnaire to assess satiety responsiveness (SR), a measure of children's tendency to stop eating once sated (trait). To assess state-based satiety, the Satiety Quotient (SQ) was calculated from an ad-libitum laboratory meal [(Pre-meal hunger – post-meal hunger)/meal intake in grams]. A higher SQ indicates a greater reduction in hunger per gram (i.e., better satiety responsiveness). Results: Overall, SR and SQ were not correlated ( P = 0.57). However, a linear regression controlling for pre-meal hunger and child BMI percentile revealed a risk status-by-SR interaction (β = 0.804, P = 0.04) such that SR was positively associated with SQ in high-risk children (95% CI [0.003, 0.430]), but there was no relationship between SR and SQ in low-risk children (95% CI [−0.203, 0.085]). No differences in SR, SQ, pre-meal hunger, or post-meal hunger were observed between risk groups. Conclusions: Parentally reported (trait-based) satiety was positively associated with laboratory-assessed satiety, but only among healthy weight children at high-familial risk for obesity. Parents of children who are at high-risk for developing obesity may be more observant of children's appetitive traits compared to parents of low-risk children, and this may be helpful in the prevention of obesity. Funding Sources: NIH RO1: DK110060.